Morbidity among Israeli backpack travelers to tropical areas. Issue 45 (January 2022) - Kaplan, Shiran; Khoury, Sobhi; Zaidenstein, Ronit; Cohen, Erica; Tischler-Aurkin, Dinnie; Sheffer, Rivka; Lewis, Matthew; Mor, Zohar
Abstract: Background: Travelers to tropical areas may be susceptible to illness or injuries. This study aims to assess morbidity among travelers during their travel and compare those who became ill or were injured with those who did not. Methods: This prospective study included 400 travelers who were counselled by a physician in pre-travel clinics in central Israel between 2017 and 2018. Participants were interviewed within a month after their return regarding morbidity during travel, including health problems that started one week following their return. Results: Most travelers (N = 320, 80%) reported at least one illness or injury. Illnesses/injuries were more common among females than males (84.9% vs. 75.1%, p = 0.01), travel periods longer than 30 days (87.7% vs. 77.2%, p = 0.03), and travelers accompanied by their friends or solo travelers compared with those who traveled with their family/partner (83.8% and 70.0%, respectively, p = 0.002). The most common complaint was diarrhea (N = 159, 49.6%), followed by high-altitude sickness (N = 118, 36.9%) and fever (N = 100, 31.2%). Altitude sickness symptoms were more common in females than in males (58.9% vs. 41.0%, p = 0.006) and in those who ascended rapidly in comparison to those who ascended gradually (58.7% vs. 44.6%, p = 0.04). Animal injury was reported by 30 (7.5%) participants yet only eight (27.0%) received medical care, seven of whom (23.3%) were vaccinated against rabies. Conclusions: Being a female, traveling with friends or alone and longer travel periods were associated with illness/injury. Practitioners at pre-travel clinics should inform travelers of the possible risks including the potential severe consequences of rabies and altitude sickness.